Understanding the Effect of Reflow Profile on the Metallurgical Properties of Tin–Bismuth Solders - Karel Dušek; David Bušek; Petr Veselý; Anna Pražanová; Martin Plaček; Julia Del Re (Metals, 2022)
Sn–Bi alloys are desirable candidates for soldering components on printed circuit boards (PCBs) because of their low melting point and reduced cost. While certain tin–bismuth solders are well characterized many new alloys in this family have been developed which need proper characterization. The following study looks at the behavior of four different Sn–Bi alloys—traditional 42Sn58Bi and 42Sn57Bi1Ag and two new tin–bismuth alloys—in solder paste during the reflow soldering process. Each alloy was processed using different reflow profiles that had varying times above liquidus (TALs) and peak temperatures. The PCBs were then analyzed to see how the processing variables influenced wetting, voiding, microstructure, intermetallic layer composition, and thickness. After analysis, the PCBs were then subjected to thermal cycling experiments to see how reflow profile impacted microstructure evolution. The results demonstrated that reflow profile affects properties such as metal wetting and voiding. It does not however, greatly impact key metallurgical properties such as intermetallic layer thickness.